Teacher’s Experience on Using English as Medium of Instruction for Science in Islamic Educational Context - Ramadhana, Diba (Sintuwu Maroso Journal of English Teaching, 2025)
This study explores the lived experiences of a science teacher implementing English Medium Instruction (EMI) in an Indonesian Islamic elementary school. Amid the global push for EMI, it examines the often-overlooked intersection of pedagogical, linguistic, and cultural-religious pressures faced by educators in such unique contexts. Using a qualitative phenomenological approach, the study analyzes data from a semi-structured interview to understand the teacher’s challenges and meaning-making processes. Findings reveal three key themes: (1) the teacher’s daily experience as a constant balancing act between delivering science content and teaching in English; (2) the navigation of significant linguistic, pedagogical, and emotional challenges; and (3) the intentional effort to reconcile English instruction with Islamic values, framing EMI as a means to cultivate a “Global Muslim” identity. The study argues that the teacher functions as an intuitive, culturally responsive agent, employing strategies like translanguaging to bridge global educational demands and local cultural values. The study concludes that effective EMI implementation in culturally diverse settings must go beyond focusing solely on language proficiency. It calls for policies and professional development that support teachers in their complex roles as cultural mediators. These insights have implications for designing context-sensitive educational programs that empower teachers working at the intersection of global and local educational expectations.